Introducing Iqbal the Economist (The Pakistan Development Review, 2001)
The Iqbal Memorial Lecture was instituted in 1994 when the Pakistan Society of Development Economists (PSDE) celebrated the completion of a decade of steady progress. A brief announcement stated: “The Iqbal Memorial Lecture attributed to the national poet [Emphasis added], Allama Muhammad Iqbal has been included in the programme for the first time. Professor Ian M. D. Little is delivering that lecture” [Secretary’s Report (1994), p. 1472]. Iqbal, the poet and philosopher par excellence, has made incisive remarks or comments on economic and social issues in his poetry, philosophical writings, and in the course of his discourses as well as some famous letters, particularly those written to the Quaid-i-Azam, Muhammad Ali Jinnah, the founder of Pakistan. But these do not make Iqbal an economist. The Secretary of the PSDE was, therefore, careful in observing that the lecture commemorates our “national poet”. However, it will be of great interest to this largest national congregation of economists and other scholars concerned with development to know that the very first published book of Iqbal related neither to poetry nor philosophy, but economics. It was written in Urdu. He also taught the subject at undergraduate and Master’s level, even though he had not studied it as a student. At the Government College, Lahore, Iqbal studied English, Philosophy and Arabic for his B.A. and then completed the M.A. in Philosophy.